Study of radon content in the air of premises on the territory of some administrative districts in the Vitebsk region - Zhuk, Ihar V.; Lukashevich, Jana A.; Vasileuski, Leu L.; Hakimov, Dilshod A.; Sosnovskiy, Alyaksei V.; Lisyanovich, Tatyana V. (Journal of the Belarusian State University. Ecology, 2021)
Unchanged concentrations of uranium-238, radium-226 in naturally soils and rocks are the source of radon. At least 40 % of territory of the Republic of Belarus is potentially radon risk.. At the same time radon and radioactive decay products make the main contribution to the radiation background of residential and industrial premises. It is cause of the systematic radon monitoring. Such systematic radon monitoring in the air of premises in the Republic of Belarus has been carried out by the scientific institution «JIPNR-Sosny» since 2002. The object of research is the volumetric activity of radon in the air of residential and industrial premises. In accordance with the recommendations of the International Commission on Radiation Protection, measurements of the volumetric activity of radon in the air of the premises of the Republic of Belarus are carried out by the integral method of passive track radiometry using solid-state track nuclear detectors of alpha particles. The results of radon monitoring in the air in 36 settlements of 9 administrative districts in the Vitebsk region in October 2016 – February 2017 are presented. It was carried out in order to increase the statistics of research for the Vitebsk region. A variety of building materials, their type, number of floors were taken into account as criteria for choosing of settlement,. The total number of studied premises was 264. It were 228 residential and 36 public and industrial premises among them. Annual average radon equivalent equilibrium volumetric activities were determined using the measured volumetric activities of radon and the corresponding methodological instructions. Geographical and spatial analyses of the radon concentrations measurements in residential premises were performed.